The PREgnancy and FERtility (PREFER) Study Investigating the Need for Ovarian Function and/or Fertility Preservation Strategies in Premenopausal Women With Early Breast Cancer - Blondeaux, Eva; Massarotti, Claudia; Fontana, Valeria; Poggio, Francesca; Arecco, Luca; Fregatti, Piero; Bighin, Claudia; Giannubilo, Irene; Ruelle, Tommaso; Razeti, Maria Grazia; Boni, Luca; Anserini, Paola; et al. (Frontiers in Oncology, 2021)
Background: Offering ovarian function and/or fertility preservation strategies in premenopausal women with newly diagnosed breast cancer candidates to undergo chemotherapy is standard of care. However, few data are available on uptake and main reasons for refusing these options. Methods: The PREFER study (NCT02895165) is an observational, prospective study enrolling premenopausal women with early breast cancer, aged between 18 and 45 years, candidates to receive (neo)adjuvant chemotherapy. Primary objective is to collect information on acceptance rates and reasons for refusal of the proposed strategies for ovarian function and/or fertility preservation available in Italy. Results: At the study coordinating center, 223 patients were recruited between November 2012 and December 2020. Median age was 38 year (range 24 – 45 years) with 159 patients (71.3%) diagnosed at ≤40 years. Temporary ovarian suppression with gonadotropin-releasing hormone agonists (GnRHa) was accepted by 58 out of 64 (90.6%) patients aged 41-45 years and by 151 out of 159 (95.0%) of those aged ≤40 years. Among patients aged ≤40 years, 57 (35.8%) accepted to access the fertility unit to receive a complete oncofertility counseling and 29 (18.2%) accepted to undergo a cryopreservation technique. Main reasons for refusal were fear of delaying the initiation of antineoplastic treatments and contraindications to the procedure or lack of interest in future childbearing. Patients with hormone-receptor positive breast cancer had higher acceptance rates of ovarian function and/or fertility preservation strategies than those with hormone-receptor negative disease. Conclusions: More than 90% of premenopausal women with early breast cancer, and particularly those with hormone receptor-positive disease, were concerned about the potential risk of chemotherapy-induced premature ovarian insufficiency and/or infertility and accepted GnRHa administration. Less than 1 out of 5 women aged ≤40 years accepted to undergo cryopreservation strategies.